2003
DOI: 10.2165/00126839-200304010-00002
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Rebamipide as Adjunctive Therapy in the Treatment of Recurrent Oral Aphthous Ulcers in Patients with Beh??et??s Disease

Abstract: Rebamipide is well tolerated and improves the aphthae count and pain score in BD patients. It may therefore be useful in the treatment and prevention of frequently recurrent oral aphthous ulcers (not restricted to BD). Administration of rebamipide is not cumbersome, and it does not cause any discomfort, which corticosteroid ointments for example may do; furthermore, there are no specific adverse drug reactions. Rebamipide is therefore recommended as a long-term treatment for recurrent oral aphthous ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
50
1
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 11 publications
2
50
1
8
Order By: Relevance
“…In an epidemiological survey it was concluded that minor aphthous ulcer is the most common type of RAS and constitutes about 80%. Major aphthous ulcer is about 13% and herpetic form 7% in accordance with the present study [11]. In a study it was documented that minor aphthous ulcer constitutes 75-85% of total RAS cases whereas major aphthous ulcer is about 10-15% and herpetiform type is the smallest group with only 5% [13].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In an epidemiological survey it was concluded that minor aphthous ulcer is the most common type of RAS and constitutes about 80%. Major aphthous ulcer is about 13% and herpetic form 7% in accordance with the present study [11]. In a study it was documented that minor aphthous ulcer constitutes 75-85% of total RAS cases whereas major aphthous ulcer is about 10-15% and herpetiform type is the smallest group with only 5% [13].…”
Section: Discussionsupporting
confidence: 92%
“…In another study prevalence of RAS was seen in patients below the age of 10 y, whereas no patients were reported below the age of 10 years in the present study [12]. In another study it was documented that in about 80% of patients with RAS the condition develops before 30 y of age and the onset in later years suggests a possibility of definite predisposing factor leading to RAS or that ulceration is not simple RAS, but rather a part of more complex disorder such as Behcet's disease [11].…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations